Climate Resilient Varieties and Technologies of Tropical Tuber Crops in Northeastern Region - Byju, G; Jaganathan, D (Indian Horticulture, 2024)
In Northeast India, the tuber crops are considered an important source of food and nutritional security, income generation, employment and animal feed. The tuber crops have also proved to be life sustaining crops in times of natural calamities and famine. It is also worth noting that tropical tuber crops such as cassava and yams can cope with climate vagaries such as drought, high temperature and salinity which qualify them to be dubbed as ‘climate resilient’ or ‘future smart crops’. With improved technologies, these groups of crops are becoming future smart crops not only for food and nutrition but also to build agro-enterprises to foster inclusive growth in Northeastern India.